2021
DOI: 10.1344/did.2021.10.37-54
|View full text |Cite
|
Sign up to set email alerts
|

Educación STEAM en educación infantil: Un acercamiento a la ingeniería

Abstract: En este trabajo planteamos la conveniencia de desarrollar las competencias relacionadas con la Educación STEAM (CTIAM, en castellano) por medio de contextos ricos que favorezcan el aprendizaje. En particular, mostramos cómo el uso de problemas relacionados con la ingeniería, adaptados a las edades de niños y niñas de educación infantil (4 y 5 años), y planteados desde el enfoque de la Educación Matemática Realista, favorece el desarrollo, entre otras cosas, de la competencia matemática, permitiendo trabajar no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In this sense, a future line of research would be to extend the field study to a larger sample in order to analyze the results shown here form a quantitative point of view. Thus, as Berciano et al (2021) proposed the suitability of the treatment of engineering in the early childhood classroom from a STEAM approach, it cannot be overlooked that this work allows us to conclude that, based on a scientific questioning adapted to the early childhood classroom (with three-year-old children), it has been proven that not only do different mathematical contents emerge, but also that, during the process of justifying the answer, children activate communication and reasoning mechanisms involving different standards of mathematical processes, thus highlighting the need to design and include this type of STEAM contexts in the classroom in order to develop mathematical competence.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In this sense, a future line of research would be to extend the field study to a larger sample in order to analyze the results shown here form a quantitative point of view. Thus, as Berciano et al (2021) proposed the suitability of the treatment of engineering in the early childhood classroom from a STEAM approach, it cannot be overlooked that this work allows us to conclude that, based on a scientific questioning adapted to the early childhood classroom (with three-year-old children), it has been proven that not only do different mathematical contents emerge, but also that, during the process of justifying the answer, children activate communication and reasoning mechanisms involving different standards of mathematical processes, thus highlighting the need to design and include this type of STEAM contexts in the classroom in order to develop mathematical competence.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, for the development of mathematical argumentation in childhood, the role of adults is crucial (Nergard, 2023) and for mathematical learning to be meaningful, it must be treated in a holistic way. The contents must be worked on through problemsolving processes and reasoning through classroom activities that encourage the construction of knowledge, and the posing of problems, where varied strategies can be applied and adapted (Berciano et al, 2017). In this teaching and learning context, teachers should plan and manage classroom activities considering mathematical processes such as reasoning and proof (Alsina, 2016), motivating students to reflect on their answers, so that they provide explanations and justifications that allow them to understand the true meaning of mathematics (NCTM, 2003;Salgado et al, 2020).…”
Section: Mathematical Argumentation In Early Childhood Educationmentioning
confidence: 99%
See 2 more Smart Citations